Evaluasi Program Pemerintah Kota Tomohon Terhadap Pengurangan Sampah Plastik Di Kelurahan Kampung Jawa - Wanget, Samuel Wailan Leonard; Taasiringang, Gloria; Daluwu, Frisca Jellyani; Agama, Harlinda; Gumansalangi, Prisca; Sasehang, Juandry; Wasida, Marchella; Auif, Rut Serina; Mandalika, Tesalonika; Sumenda, David Chara; Tarelluan, Samantha; Taarae, Kesya; Mamarodia, Laidy Tirsa; Tamusa, Myrina Monika; Poli, Paulina Gledis; Larengkeng, Veronika; Wattimena, Priskila Julia (PT. Giat Konseling Nusantara, 2024)
Tomohon, renowned for its spotless and beautiful environment, is often referred to as the